The Influence of Investment Knowledge, Technological Advancement, Investment Motivation on Investment Interest in the Capital Market (Study on Students of the Faculty of Economics and Business, Gunung Jati University of Cirebon) - Nurhidayah, Ariska; Putri Sabilla, Ghina; Hidayat, Firman (DINASTI RESEARCH, 2025)
This study aims to examine the influence of investment knowledge, technological advancements, and investment motivation on students' interest in capital market investment. The research focused on students from the Faculty of Economics and Business at Swadaya Gunung Jati University in Cirebon. A quantitative approach was employed, collecting data from 338 respondents using purposive sampling and analyzed through multiple linear regression techniques. The results indicate that investment knowledge, technological advancements, and investment motivation have a significant and positive effect on students’ investment interest, both jointly and individually. Among the three variables, investment motivation is found to be the most influential factor. These findings highlight the importance of improving financial literacy, embracing digital technologies, and fostering internal motivation to encourage greater student participation in capital market activities. This study offers useful insights for educational institutions and policymakers in designing effective strategies to promote student engagement and awareness regarding investment opportunities in the capital market.